Lateral Bearing Trait in Indian Walnut (Juglans regia L.) Germplasm: a Potential Yield Contributing Trait in Early Age of the Tree - Chand, L.; Singh, D. B.; Sharma, O. C.; Mir, J. I.; Kumawat, K. L.; Rai, K. M.; Rather, S. A.; Qureshi, I.; Lal, S.; Dev, Inder (International Journal of Bio-resource and Stress Management, 2017)
The present study was carried out during year 2015 and 2016 at ICAR-Central Institute of Temperate Horticulture (CITH), Srinagar, India with the objective of trait specific characterization of walnut accessions with specific emphasis on lateral bearing trait. The study was initiated on pre-selected indigenous accessions collected from various pockets of North Western Himalaya and maintained at field gene bank of the institute. The most widely grown varieties ‘Sulaiman’ and ‘Hamdan’ were used as local check. All the accessions were monitored to identify the bearing habit. Only one accession CITH-W-121 (IC-0622836) was found with lateral bearing trait, which had fruit bearing on leafy shoots emerging from terminal, sub terminal as well as from lateral buds of 1-year-old shoot. Bearing on lateral leafy shoots developing from lateral buds of 1-year-old shoot is being reported for the first time in indigenous genetic resources of walnut which is an important trait to improve productivity. Lateral leafy shoots emerged all along 1-year old shoot, in which about 50% lateral leafy shoots bearing 1−3 fruits panicle-1. Overall 40−60% lateral leafy shoots in a tree were bearing fruits in this accession. In term of yield, CITH-W-121 (11.07 kg tree-1) was found significantly superior to Sulaiman (5.85 kg tree-1) and Hamdan (5.48 kg tree-1). Yield efficiency was recorded significantly higher in CITH-W-121 (26.37 g cm-2 tcsa) over the two ruling check varieties i.e, Hamdan (13.99 g cm-2 tcsa) and Sulaiman (9.65 g cm-2 tcsa). In accession CITH-W-121, nut weight and kernel weight was recorded on par with Hamdan, while kernel recovery was on par with Sulaiman. This accession has desirable traits like well filled, plump and light coloured kernel with moderately easy removal of kernel halves and is having a good balance between vegetative growth and fruit bearing.